2016
DOI: 10.3390/ijerph13070661
|View full text |Cite
|
Sign up to set email alerts
|

How and Why Do Smokers Start Using E-Cigarettes? Qualitative Study of Vapers in London, UK

Abstract: The aims of the study were to (1) describe how and why smokers start to vape and what products they use; (2) relate findings to the COM-B theory of behaviour change (three conditions are necessary for behaviour change (B): capability (C), opportunity (O), and motivation (M)); and (3) to consider implications for e-cigarette policy research. Semi-structured interviews (n = 30) were conducted in London, UK, with smokers or ex-smokers who were currently using or had used e-cigarettes. E-cigarette initiation (beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 26 publications
1
54
1
2
Order By: Relevance
“…All accounts in these focus groups of first-time use of e-cigarettes included specific individuals, friends or family who influenced the initial trial. Consistent with previous research, 5,21 this study underscores the rule of social acceptability, “social opportunity,” and perceived improved social image in e-cigarette use. Given the importance of social influence on e-cigarette initiation, 14 continuous monitoring of social climate surrounding e-cigarette use and marketing will inform regulation policy, enforcement, and health communication.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…All accounts in these focus groups of first-time use of e-cigarettes included specific individuals, friends or family who influenced the initial trial. Consistent with previous research, 5,21 this study underscores the rule of social acceptability, “social opportunity,” and perceived improved social image in e-cigarette use. Given the importance of social influence on e-cigarette initiation, 14 continuous monitoring of social climate surrounding e-cigarette use and marketing will inform regulation policy, enforcement, and health communication.…”
Section: Discussionsupporting
confidence: 89%
“…4 A study of British smokers who had used e-cigarettes showed that initiation of e-cigarette use was influenced by social and psychological factors, such as using e-cigarettes with friends and family and the belief that e-cigarettes were less harmful than combustible cigarettes. 5 …”
mentioning
confidence: 99%
“…Studies have revealed that most believe that ECs are less harmful than cigarettes and even some believe that they are harmless [11][12][13][14] . Even when EC users have concerns about safety, there is a pervasive belief that ECs are a healthier alternative to cigarettes and that the harmful effects of cigarettes outweigh the consequences of EC use 12,15 . A study of health-care professionals and cessation counselors found that 83% believed ECs were healthier than cigarettes but still did not recommend them as a cessation technique; however recent evidence suggests that this positive belief is waning 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Evidence indicates that healthcare providers are divided on EC-use-area prohibition with wide ranges of 16% to 62% favoring use in cigaretteprohibited areas 16,22 . The belief that ECs can be used indoors or where cigarettes are prohibited, such as in schools or at work, is appealing to smokers 8,11,13,15 . One study found that EC experimentation was 4 times higher in groups that believed ECs could be used anywhere 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation